2016
DOI: 10.1186/s12886-016-0345-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of vernal keratoconjunctivitis among children in Gondar city, Northwest Ethiopia

Abstract: BackgroundVernal keratoconjunctivitis (VKC) is a common cause of ocular morbidity in children in warm dry climates such as Sub–Saharan Africa and accounts for about 3 % of serious ophthalmic cases in tropical countries. The purpose of this study was to assess the prevalence and associated factors of vernal keratoconjunctivitis among children living in Gondar City, Ethiopia.MethodsA Cross Sectional Design study was carried out in 737 children under the age of 18 years in Gondar City from April to May 2015. Basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 13 publications
(11 reference statements)
5
29
0
Order By: Relevance
“…7 The Hayilu D et al also found an association between family history of non-ocular allergic disease such as asthma, atopic rhinitis and VKC. 11 In present study, the most common presenting feature of itching (100%) supports the dictum, 'no itching, no vernal catarrh'. Apart from this, redness was found in 96 (61.93%) patients, watering in 78 (50.32%) patients and thick discharge in 65 (41.93%) patients.…”
Section: Discussionmentioning
confidence: 57%
“…7 The Hayilu D et al also found an association between family history of non-ocular allergic disease such as asthma, atopic rhinitis and VKC. 11 In present study, the most common presenting feature of itching (100%) supports the dictum, 'no itching, no vernal catarrh'. Apart from this, redness was found in 96 (61.93%) patients, watering in 78 (50.32%) patients and thick discharge in 65 (41.93%) patients.…”
Section: Discussionmentioning
confidence: 57%
“…The prevalence of VKC varies greatly and increases with vicinity to the equator. In Scandinavian countries, prevalence is close to 0%, whereas it reaches 0.27% in Italy and is higher still in Africa, with a reported prevalence of 6% in Ethiopia . Although the causes of VKC are still unclear, there is a strong correlation with exposure to sunlight, which exacerbates the disease …”
Section: Introductionmentioning
confidence: 99%
“…There are three forms of VKC tarsal, limbal, and mixed. The tarsal form is characterized by the presence of papillae in the upper tarsal lid, and the limbal form by gelatinous infiltrate in the limbus and Horner‐Trantas dots …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is relatively rare in Western Europe 11 but the prevalence and severity increases in warm climates. 12 Classically it presents in the spring pollen season, but acute exacerbations can occur at any time after exposure to allergens. In vernal keratoconjunctivitis, goblet cells are increased, causing copious mucus production.…”
Section: Rarer Causesmentioning
confidence: 99%